Challenges in imaging cell surface receptor clusters. (January 2016) - Medda, Rebecca; Giske, Arnold; Cavalcanti-Adam, Elisabetta Ada
Abstract: Super-resolution microscopy offers unique tools for visualizing and resolving cellular structures at the molecular level. STED microscopy is a purely optical method where neither complex sample preparation nor mathematical post-processing is required. Here we present the use of STED microscopy for imaging receptor cluster composition. We use two-color STED to further determine the distribution of two different receptor subunits of the family of receptor serine/threonine kinases in the presence or absence of their ligands. The implications of receptor clustering on the downstream signaling are discussed, and future challenges are also presented. Highlights: Ring-like structure of BMP receptor subunit IB revealed by STED microscopy. BMP receptor subunits IB and II show different localization patterns. BMP receptor II joins BMP receptor IB clusters upon BMP-2 addition.